PENAMBAHAN BERBAGAI KONSENTRAT PADA SILASE LIMBAH KOL DAN SAWI TERHADAP NILAI FISIK, pH DAN JUMLAH POPULASI BAKTERI ASAM LAKTAT - Adelina, Triani; Juliantoni, Jepri; Harahap, Anwar Efendi; Ali, Arsyadi; Anyanur, Muammar Reza (Jurnal Nutrisi Ternak Tropis dan Ilmu Pakan, 2024)
Cabbage + mustard greens in the form of waste usually contain high water content so they have the potential to be used as silage feed through the addition of various concentrates. The aim of the research was to assess the physical quality, pH and number of lactic acid bacteria colonies of cabbage + mustard greens waste silage to which different types of concentrate were added. The research used the RAL method with 4 treatments and 5 replications. The treatments are: S1 = 70% cabbage and mustard silage plus 30% rice bran; S2 = 70% cabbage and mustard silage plus 30% corn flour; S3 = 70% cabbage and mustard greens silage plus 30% onggok; and S4 = 70% cabbage and mustard silage plus rice bran + corn flour + 30% onion. The results of the research showed that physical silage, pH and number of LAB colonies produced the same conditions (P>0.05) as cabbage + mustard greens waste silage, whereas based on pH measurements it showed that the addition of rice bran concentrate and corn flour was superior to the use of onggok concentrate.  The conclusion was that cabbage + mustard greens waste silage added from various sources was able to increase the physical value of the silage, pH and the number of lactic acid bacteria populations